RECLAMATION OF Imperata Grassland USING COFFEE BASED AGROFORESTRY: IMPACTS ON WATER INFILTRATION - Ardiansyah, Nanda; Aldini, Leony Siska; Putra, Arega Dwi; Pradani, Avi Qurvanda Putri; Ishaq, Rizki Maulana; Saputra, Danny Dwi; Hairiah, Kurniatun (Jurnal Tanah dan Sumberdaya Lahan, 2025)
The spread of Imperata cylindrica in agricultural lands is often associated with a decline in soil fertility, causing crops to be outcompeted by Imperata cylindrica. This study aimed to evaluate land cover, litter biomass, and soil infiltration rates in lands previously occupied by Imperata cylindrica that had been reclaimed with coffee-based agroforestry in Nagari Sirukam, Solok Regency, West Sumatra. The survey on volcanic soils was conducted in July-August 2024. The results showed that natural remnant forests (HT) had the highest canopy cover at 69%, while multistrata  agroforestry (AFMT) had a canopy cover of 37%. The highest standing litter was found in multistrata agroforestry (3.1 Mg ha-1), while at HT had 0.6 Mg ha-1 only. The highest infiltration rate was found in Imperata cylindrica grassland (AF0) with 0.072 cm sec-1, due to the dense rhizomes, while multistrata agroforestry had an infiltration rate that was 73% lower (averaged 0.02 cm sec-1). Although the infiltration rate was lower, agroforestry combined with fire control was effective in maintaining soil stability, reducing erosion, and improving soil quality sustainably, providing long-term benefits for soil and water conservation.